Construction and Characterization of a New Recombinant Vector to Remove Sulfate Repression of dsz Promoter Transcription in Biodesulfurization of Dibenzothiophene - Khosravinia, Somayeh; Mahdavi, Mahmood A.; Gheshlaghi, Reza; Dehghani, Hesam; Rasekh, Behnam (Frontiers in Microbiology, 2018)
Biodesulfurization (BDS) is an environmentally friendly desulfurizing process with the potential of replacing or adding to the current expensive technologies for sulfur removal from fossil fuels. The BDS, however, still suffers from low biocatalyst activity. One reason is repression of dsz promoter transcription in presence of inorganic sulfate that impedes translation of Dsz enzymes required for desulfurization pathway. One approach to solve this problem is replacing the native promoter with a new promoter that is no longer repressed. In this study, dsz genes from desulfurizing strain Rhodococcus sp. FUM94 was cloned in an alkane responsive promoter, pCom8, and expressed in E. coli BL21 (DE3) as a host. The recombinant was not susceptible to inorganic sulfate in the culture medium. Desulfurizing activity of recombinant strain versus wild type indicated that in a sulfate containing medium, BDS yield of recombinant increased from 16.0%±0.9 to 34.0%±1.9% when dibenzothiophene (DBT) concentration (dissolved in ethanol) increased from 25 ppm through 100 ppm. Also, 2-hydroxy biphenyl (2HBP) production rate improved 8.5-fold (from 0.302±0.020 to 2.57±.14 mmol 2-HBP (kg DCW)-1h-1) at the same DBT concentration range. This is while no 2HBP production was detected in FUM94 biphasic reaction. In a sulfate-free medium, wild type strain demonstrated desulfurization activity, but decreasing with the increase of DBT concentration dissolved in n-tetradecane. Whereas, the recombinant strain demonstrated increasing desulfurizing activity in a sulfate-containing high DBT concentration environment. Overall, the result of this molecular manipulation can be considered as a step forward towards commercialization of BDS technology.